Determinan Kecurangan dalam Perspektif Fraud Hexagon dengan Religiusitas sebagai Variabel Moderasi - Ferina, Ika Sasti; Budiman, Anton Indra; Aspahani, Aspahani (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the determinants of fraud in the fraud hexagon perspective with religiosity as a moderating variable. The population of this study was all Regional Apparatus Organizations (RAOs) in South Sumatra Province, totaling 34 RAOs. Data collection was carried out through questionnaires given to Commitment Making Officers (CMOs) and Technical Activity Implementing Officers (TAIOs) in various Regional Apparatus Organizations in South Sumatra Province. This study is a quantitative descriptive study using the Structural Equation Model-Partial Least Square approach through SmartPLS. The results of this study reveal that the variables of pressure, opportunity, rationalization, collusion do not have a significant effect on fraud in the procurement of goods and services. However, the variables of competence and arrogance have a significant effect on fraud in the procurement of goods and services in Regional Apparatus Organizations (RAOs) in South Sumatra Province. In addition, it was also found that the variable of religiosity was unable to strengthen or weaken the influence of pressure and opportunity on fraud in the procurement of goods and services. in Regional Apparatus Organizations (RAOs) in South Sumatra Province.